Implementasi Pendataan Awal Registrasi Sosial Ekonomi Guna Pemutakhiran Data Kondisi Sosial Ekonomi Terpadu di Kabupaten Karanganyar - Ningsih, Yuliana Ristantya; Alifian, Rizky (Universitas Syiah Kuala, 2025)
This study aimed to understand how the Initial Socio-Economic Registration data collection was carried out and to identify the obstacles encountered during its implementation in Karanganyar Regency. Methodology/approach: This study is a survey-based research with a mixed methods approach with a concurrent embedded design. Qualitative and quantitative data were collected in the same time period, but the qualitative approach was predominantly used in this study. The research was conducted at BPS Karanganyar Regency as the main implementing agency of the Initial Socio-Economic Registration Data Collection activities at the kabupaten level. The research data sources used were primary and secondary data. Data collection was conducted through semi-structured interviews with seven key informants (Coordinator, Koseka, PML, and PPL), as well as documentation of regulations, BPS technical guidelines, and regional archives. Data validity was maintained by triangulation between primary and secondary sources. Qualitative data were analyzed using the Miles Huberman interactive model, while quantitative data were analyzed using multiple linear regression. Results/findings: Using George Edward III's implementation theory, the study found that not all implementation variables were met. Key unmet variables included clarity in communication and the adequacy of human resources. Major internal obstacles included late instructions from the central government causing time pressure, insufficient quality of field officers, ineffective training for these officers, and unclear information dissemination to residents. Key external obstacles were public misperception of data collectors and difficulty locating residents.Contribution: This study contributes valuable insights for policymakers and implementing agencies (like BPS at various levels) involved in large-scale socio-economic data collection and social protection programs. It highlights critical practical obstacles in public policy implementation, particularly concerning data collection processes and human resource management in the context of public administration and statistic.